Bridging divides : ethno-political leadership among the Russian Sámi - Øverland, Indra (Berghahn Books, 2012)
The Sámi are a Northern Indigenous people whose land, Sápmi, covers territory in Finland, Norway, Russia and Sweden. For the Nordic Sámi, the last decades of the 20th century saw their Indigenous rights partially recognized, a cultural and linguistic revival and the establishment of Sámi parliaments. The Russian Sámi, however, did not have the same opportunities and were isolated behind the closed border until the dissolution of the Soviet Union. This book examines the following two decades and the Russian Sámi's attempt to achieve a linguistic revival, to mend the Cold War scars, and to es.